Abnormal Structure of von Willebrand Factor in Myeloproliferative Syndrome Is Associated to Either Thrombotic or Bleeding Diathesis - López-Fernández, M F; López-Berges, C; Martín, R; Pardo, A; Ramos, F J; Batlle, J (Thrombosis and Haemostasis, 1987)
The multimeric and subunit patterns of plasma von Willebrand factor (vWF) were analyzed in eight patients with myeloproliferative syndrome (MS) in order to investigate the possible existence of heterogeneity in the “in vivo” proteolytic cleavage of the protein, previously observed in this entity. Six patients lacked large vWF multimers, five of them having normal bleeding times (BT) and clinically documented episodes of thrombotic origin, whereas one patient had long BT and bleeding symptoms. Seven patients showed a relative increase in the 176 kDa subunit fragment while the 189 kDa polypeptide was increased in only one. In addition, another patient (and prior to any therapy) showed the presence of a new fragment of approximately 95 kDa which disappeared after Busulfan therapy. The collection of blood from these patients with proteinase inhibitors did not correct the abnormalities.The infusion of DDAVP to two patients with abnormal vWF was accompanied by: the appearance of larger vWF multimers which disappeared rapidly from plasma; an increase in the relative proportion of the satellite bands of each multimer and a further increase of the 176 kDa fragment. These data point to some heterogeneity in the vWF abnormality present in MS which may be related in part to a variable degree of proteolysis of vWF occurring “in vivo” rather than “in vitro”, and which may be associated to either a thrombotic or a bleeding diathesis. They also suggest that despite the presence of abnormal, already proteolyzed vWF, DDAVP-enhanced proteolysis occurs in MS to a similar extent to what is described in normal individuals.
Keywords: von Willebrand factor; Myeloproliferative syndrome -DDAVP; Desmopressin